Effectiveness of Dream Therapy on Anxiety in Patients with Irritable Bowel Syndrome: A Strategy to Enhance Quality of Life - Pooyan, Shaghayegh; Atashpour, Seyed Hamid (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study was conducted to evaluate the effectiveness of dream therapy on anxiety in patients diagnosed with Irritable Bowel Syndrome (IBS), as a strategic approach to enhancing their quality of life. Methods and Materials: The present research employed a semi-experimental clinical trial design with a control group. Following initial assessments and confirmation of inclusion criteria, participants were randomly assigned to two groups of 15 individuals each: an experimental group (receiving dream therapy) and a control group (waitlist). Inclusion criteria included a formal diagnosis of IBS based on the Rome III criteria, a minimum educational qualification of a high school diploma, being within the age range of 20–55 years, and scoring above the clinical cutoff on the Beck Anxiety Inventory (BAI). The experimental group received a dream therapy intervention across twelve 120-minute sessions. The measurement instrument was the Beck Anxiety Inventory (BAI), which was administered to both groups at pre-test and post-test stages. Data analysis was conducted at the level of inferential statistics using analysis of covariance (ANCOVA) via SPSS version 26. Findings: The results indicated that dream therapy significantly reduced anxiety levels in the experimental group compared to the control group (P < 0.005). The effect size (group effect) was reported as 0.262, with a statistical power of 0.848. Conclusion: These findings suggest that dream therapy can serve as an effective intervention for reducing anxiety in patients with Irritable Bowel Syndrome and, consequently, improving their quality of life.